2010
DOI: 10.3109/19396368.2010.509902
|View full text |Cite
|
Sign up to set email alerts
|

Di-n-Butyl Phthalate (DBP) Exposure Induces Oxidative Damage in Testes of Adult Rats

Abstract: Di-n-butyl phthalate (DBP) is a ubiquitous environmental pollutant, extensively used as a plasticizer in many products including plastics, cosmetics, and medical devices. Some studies have shown that DBP has potential testicular toxicity. However, the mechanism of action of DBP on male reproduction is not clear. The present study was designed to further investigate the potential male reproductive toxicity of DBP . Oxidative stress was assessed in rat testes as an underlying mechanism. Forty SD adult rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 18 publications
6
43
1
1
Order By: Relevance
“…It was reported that exposure to MBP destroyed tight junctional structure in Sertoli cell (Schettler, 2006). The reduction of sperm count and degenerated histological changes in testicular seminiferous tubules induced by MBP are similar to the results reported in previous studies (Shono and Taguchi, 2014;Zhou et al, 2010). Under normal circumstances, the oxidant and antioxidant system in organisms maintains an equilibrium state.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It was reported that exposure to MBP destroyed tight junctional structure in Sertoli cell (Schettler, 2006). The reduction of sperm count and degenerated histological changes in testicular seminiferous tubules induced by MBP are similar to the results reported in previous studies (Shono and Taguchi, 2014;Zhou et al, 2010). Under normal circumstances, the oxidant and antioxidant system in organisms maintains an equilibrium state.…”
Section: Discussionsupporting
confidence: 80%
“…Our results showed that a higher dose (200 mg/kg) of MBP exposure increased ROS level and even increased MDA content in mouse testes. DBP dosed at 250, 500 and 2,000 mg/kg also markedly decreased the testicular GSH level, along with degeneration of the seminiferous tubules (Zhou et al, 2010). The DBP-induced injuries in biochemical, spermatological parameters and histological structure of testis could be recovered by treatment with kolaviron or curcumin which have antioxidative activity (Farombi et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The main possible mechanism of toxicity is based on the oxidative stress (Zhou et al, 2010). Several studies reported that DBP induced lipid peroxidation in rat testis (Wang et al, 2004 andNair, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, approximately 50% of male infertility cases are still unexplained or idiopathic for men [2]. Male infertility is a complex disease resulting from multiple interactions between genetic and environmental factors [3][4][5]. The genetic background of male infertility has long been a concern.…”
Section: Introductionmentioning
confidence: 99%